2016
DOI: 10.1016/j.ihj.2015.10.384
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of coconut oil versus sunflower oil on cardiovascular risk factors in patients with stable coronary heart disease

Abstract: Coconut oil even though rich in saturated fatty acids in comparison to sunflower oil when used as cooking oil media over a period of 2 years did not change the lipid-related cardiovascular risk factors and events in those receiving standard medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 45 publications
4
58
1
6
Order By: Relevance
“…Supplementation of the two types of oils (SO and BNO) did not significantly change the glucose levels, which is consistent with previous studies [42,58,59].…”
Section: Discussionsupporting
confidence: 92%
“…Supplementation of the two types of oils (SO and BNO) did not significantly change the glucose levels, which is consistent with previous studies [42,58,59].…”
Section: Discussionsupporting
confidence: 92%
“…This study was conducted for 2 years with 100 coronary artery disease patients and 100 in the healthy control group with 98% follow-up. The results showed that there was no statistically significant difference in the anthropometric, biochemical, vascular function, and cardiovascular events in both groups indicating that coconut oil does not pose any additional risk for heart disease compared with a polyunsaturated fat (Vijayakumar et al, 2016).…”
Section: Health Of Coconut-consuming Populationsmentioning
confidence: 89%
“…Apesar dos possíveis efeitos da suplementação com óleo de coco na redução da adiposidade central [10][11][12] , não observa-se estes mesmos efeitos na massa gorda e percentual de gordura nos indivíduos [12][13][14] . Além disso, as pesquisas são conflitantes sobre os efeitos do consumo de óleo de coco em alterar os níveis séricos de colesterol total, HDL-c, LDL-c e triglicérides em diferentes grupos e faixas etárias 6 .…”
Section: Introductionunclassified